PENERAPAN TEORI SOSIAL PADA PENELITIAN KUALITATIF AKUNTANSI - Cindy Vinella; Jason Wibisono; Maya Rianti; Maria Ellita Ovina; Carmel Meiden (Sekolah Tinggi Pariwisata Mataram, 2022)
The purpose of this research is to provide an overview related to the application of social theory in accounting practice. This research is carried out using the Systematic Literature Review (SLR) methodological approach. To search for journals related to research topics, researchers use search keywords: